City as memory: A short biography of Srinagar - Wani, Sadaf (New Delhi Aleph Book Company, 2024)
Sirinagar (as it$1 (Bs pronounced in Kashmiri), the capital of Paradise on Earth, is known for its lush green valley and picturesque lakes, but also for its troubled past and unsettled present. Founded in 250 BCE by the Buddhist king Ashoka, Srinagar$1 (Bs chequered history is one of conquest and centuries of foreign rule, characterized by both indulgence and neglect.s